Gender Differences in Executives’ Access to Information - Inci, A. Can; Narayanan, M. P.; Seyhun, H. Nejat (Journal of Financial and Quantitative Analysis, 2017)
We provide novel evidence on gender differences in insider-trading behavior and the profitability of senior corporate executives. On average, both female and male executives make positive profits from insider trading. Males, however, earn significantly more than females in equivalent positions and also trade more than females. These gender differences disappear when we limit the sample to firms in which female trading is relatively high. Collectively, these results suggest that female executives have a disadvantage relative to males in access to inside information, even if they have equal formal status, and informal networks may play an important role in attenuating this disadvantage.